Quando as mulheres se tornam mães: a história reprodutiva feminina numa visão evolucionista - Spinelli, Luísa Helena Pinheiro (2008)
In this thesis we tested evolutionary hypotheses, with empirically collected data, in a sample composed of pregnant Brazilian women. We consider that during pregnancy and soon after the baby's birth fundamental reproductive decisions take place, given the complete feminine involvement with the reproduction phenomenon. The results are presented in four empirical articles related to the history of female reproduction. The topics approached were mate selection, the life-history theory, the strategies of parental investment and postpartum depression. Data collection was accomplished through interviews with pregnant women and after the baby s birth, with a sample composed of women from two income classes (low income and middle class), in Natal, Brazil. With respect to mate selection, the results suggest that a real situation of reproductive mate selection shows significant differences when compared to the results obtained in studies involving potential mate selection (Article I). Considering the life-history theory, we have partially confirmed the hypothesis of the father`s absence influencing the development of the young female syndrome (Article II). In regard to parental investment strategies and the decrease of fatherhood uncertainty, we identified a larger attribution of the baby's resemblance after birth with the father, confirming our hypothesis (Article III). The results related to postpartum depression occurrence partially support the hypothesis that it is an evolutionary adaptation (Article IV). This thesis is part of a consolidation movement of Evolutionary Psychology in Brazil and it presents results on female reproductive history hitherto unpublished.